Pediatric Eosinophilic Esophagitis: Results of the European Retrospective Pediatric Eosinophilic Esophagitis Registry (RetroPEER). Issue 4 (April 2019) - Hoofien, Assaf; Dias, Jorge A.; Malamisura, Monica; Rea, Francesca; Chong, Sonny; Oudshoorn, Johanna; Nijenhuis-Hendriks, Danielle; Otte, Sebastian; Papadopoulou, Alexandra; Romano, Claudio; Gottrand, Frederic; Miravet, Victor V.; et al.
ABSTRACT: Objectives: Recommendations for diagnosing and treating eosinophilic esophagitis (EoE) are evolving; however, information on real world clinical practice is lacking. To assess the practices of pediatric gastroenterologists diagnosing and treating EoE and to identify the triggering allergens in European children. Methods: Retrospective anonymized data were collected from 26 European pediatric gastroenterology centers in 13 countries. Inclusion criteria were: Patients diagnosis with EoE, completed investigations prescribed by the treating physician, and were on stable medical or dietary interventions. Results: In total, 410 patients diagnosed between December 1999 and June 2016 were analyzed, 76.3% boys. The time from symptoms to diagnosis was 12 ± 33.5 months and age at diagnosis was 8.9 ± 4.75 years. The most frequent indications for endoscopy were: dysphagia (38%), gastroesophageal reflux (31.2%), bolus impaction (24.4%), and failure to thrive (10.5%). Approximately 70.3% had failed proton pump inhibitor treatment. The foods found to be causative of EoE by elimination and rechallenge were milk (42%), egg (21.5%), wheat/gluten (10.9%), and peanut (9.9%). Elimination diets were used exclusively in 154 of 410 (37.5%), topical steroids without elimination diets in 52 of 410 (12.6%), both diet and steroids in 183 of 410 (44.6%), systemic steroids in 22 of 410 (5.3%), and esophageal dilation in 7 of 410 (1.7%). Patient refusal, shortage of endoscopy time, and reluctance to perform multiple endoscopies per patient were noted as factors justifying deviation from guidelines. Conclusions: In this "real world" pediatric European cohort, milk and egg were the most common allergens triggering EoE. Although high-dose proton pump inhibitor trials have increased, attempted PPI treatment is not universal. Abstract : Supplemental Digital Content is available in the text